2011
DOI: 10.1073/pnas.1114566109
|View full text |Cite
|
Sign up to set email alerts
|

Creation path of 35 S from Fukushima not so obvious

Abstract: In PNAS, Priyadarshi et al. (1) reported the detection of unusual levels of atmospheric 35 S in California related to releases from the Fukushima nuclear plant. The authors stated that the 35 S was generated by "leaking neutrons," activating the chlorine in the seawater that was used to cool the Fukushima reactors via the nuclear reaction 35 Cl(n,p) 35 S. The authors calculated "that 4e11 neutrons per m 2 were released," of which "2e8 neutrons per m 2 reacted with 35 Cl."Although we acknowledge it as probabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In order to interpret the results obtained in this study and to estimate the range of validity of the derived conclusions, the entire process starting at the formation of 35 S atom until deposition of 35 SO 2 or 35 SO 4 2needs to be considered. The most likely formation mechanism of the initial 35 S atom is a conversion from 35 Cl (Strub et al, 2011). The newly formed 35 S atom is oxidized to H 2 SO 4 via SO 2 and SO 3 intermediates:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to interpret the results obtained in this study and to estimate the range of validity of the derived conclusions, the entire process starting at the formation of 35 S atom until deposition of 35 SO 2 or 35 SO 4 2needs to be considered. The most likely formation mechanism of the initial 35 S atom is a conversion from 35 Cl (Strub et al, 2011). The newly formed 35 S atom is oxidized to H 2 SO 4 via SO 2 and SO 3 intermediates:…”
Section: Discussionmentioning
confidence: 99%
“…Danielache et al (2012) reported several emission scenarios based on these studies. Disagreement exist on whether the 35 S released was already present in the nuclear fuel or was produced from 35 Cl present in the primary coolant of the light wa-ter reactors (Strub et al, 2011). In addition, the seawater, which was injected into the reactor for emergency cooling, contains abundant chlorine that was converted into 35 S and released during the incident.…”
Section: Introductionmentioning
confidence: 99%
“…Although this is a remarkable result of a rather exotic radionuclide monitored in a remote station, the suggested creation path of 35 S caused some dispute . Strub et al argue that the technically unavoidable chlorine content (typically ∼0.1 ppm) of the primary coolant is a more relevant source of chlorine.…”
Section: Sulfur-35mentioning
confidence: 99%
“…46 Although this is a remarkable result of a rather exotic radionuclide monitored in a remote station, the suggested creation path of 35 S caused some dispute. 48 Strub et al argue that the technically unavoidable chlorine content (typically ∼0.1 ppm) of the primary coolant is a more relevant source of chlorine. Although this is 5 orders of magnitude below the chlorine concentration of seawater, the neutron flux density of an operating reactor is 6 orders of magnitude higher than in shut-down state.…”
mentioning
confidence: 99%
See 1 more Smart Citation